HLA-Restriction of Human Treg Cells Is Not Required for Therapeutic Efficacy of Low-Dose IL-2 in Humanized Mice - Tyagi, Rajeev K.; Jacobse, Justin; Li, Jing; Allaman, Margret M.; Otipoby, Kevin L.; Sampson, Erik R.; Wilson, Keith T.; Goettel, Jeremy A. (Frontiers in Immunology, 2021)
Regulatory T (Treg) cells are essential to maintain immune homeostasis in the intestine and Treg cell dysfunction is associated with several inflammatory and autoimmune disorders including inflammatory bowel disease (IBD). Efforts using low-dose (LD) interleukin-2 (IL-2) to expand autologous Treg cells show therapeutic efficacy for several inflammatory conditions. Whether LD IL-2 is an effective strategy for treating patients with IBD is unknown. Recently, we demonstrated that LD IL-2 was protective against experimental colitis in immune humanized mice in which human CD4+ T cells were restricted to human leukocyte antigen (HLA). Whether HLA restriction is required for human Treg cells to ameliorate colitis following LD IL-2 therapy has not been demonstrated. . Here, we show that treatment with LD-IL-2 reduced 2,4,6-trinitrobenzensulfonic acid (TNBS) reduced colitis severity in NOD.PrkdcscidIl2rg-/- (NSG) mice reconstituted with human CD34+ hematopoietic stem cells. These data demonstrate the utility of standard immune humanized NSG mice as a pre-clinical model system to evaluate therapeutics targeting human Treg cells to treat IBD.